Modulation of p53β and p53γ expression by regulating the alternative splicing of TP53 gene modifies cellular response - Marcel, V (Nature Publishing Group, 2014)
In addition to the tumor suppressor p53 protein, also termed p53α, the TP53 gene produces p53β and p53γ through alternative splicing of exons 9β and 9γ located within TP53 intron 9. Here we report that both TG003, a specific inhibitor of Cdc2-like kinases (Clk) that regulates the alternative splicing pre-mRNA pathway, and knockdown of SFRS1 increase expression of endogenous p53β and p53γ at mRNA and protein levels. Development of a TP53 intron 9 minigene shows that TG003 treatment and knockdown of SFRS1 promote inclusion of TP53 exons 9β/9γ. In a series of 85 primary breast tumors, a significant association was observed between expression of SFRS1 and α variant, supporting our experimental data. Using siRNA specifically targeting exons 9β/9γ, we demonstrate that cell growth can be driven by modulating p53β and p53γ expression in an opposite manner, depending on the cellular context. In MCF7 cells, p53β and p53γ promote apoptosis, thus inhibiting cell growth. By transient transfection, we show that p53β enhanced p53α transcriptional activity on the p21 and Bax promoters, while p53γ increased p53α transcriptional activity on the Bax promoter only. Moreover, p53β and p53γ co-immunoprecipitate with p53α only in the presence of p53-responsive promoter. Interestingly, although p53β and p53γ promote apoptosis in MCF7 cells, p53β and p53γ maintain cell growth in response to TG003 in a p53α-dependent manner. The dual activities of p53β and p53γ isoforms observed in non-treated and TG003-treated cells may result from the impact of TG003 on both expression and activities of p53 isoforms. Overall, our data suggest that p53β and p53γ regulate cellular response to modulation of alternative splicing pre-mRNA pathway by a small drug inhibitor. The development of novel drugs targeting alternative splicing process could be used as a novel therapeutic approach in human cancers.